Night Burial - Bonnici, Kate Bolton, 1979- (Book collections on Project MUSE., 2020)
"In Night Burial, Kate Bolton Bonnici mourns her mother's death from ovarian cancer by tracing the composition, decomposition, and recomposition of the maternal body. Opening with an epigraph from Julia Kristeva's "Stabat Mater," which recognizes the "abyss that opens up between the body and what had been its inside," Night Burial moves from breastfeeding to laying sod on a grave, weaving together Alabama pine forests, fairy tales, philosophy, classical and Renaissance literatures, church practices, and hospice care. Through centuries-old and newly imagined poetic forms, Night Burial crafts a haunting litany for the dead. These poems ask the essential questions of grief, intertwined with family and place: how do we address the absent beloved, and might the poem become its own conjuring whereby the I can once again speak to the you?"--